Penerapan Evidence Based Practice Pengaturan Semi Fowler pada Pasien Pneumonia - Nevi Rahel Marasi; Esther Lontoh (Yayasan Syalom Cipta Sumikolah, 2025)
The main problem in children with pneumonia is shortness of breath. Handling shortness of breath can be done by adopting a semi-Fowler position. In the semi-Fowler position, the patient is semi-sitting, where the head of the bed is higher or raised with a slope of 30°-45° and uses gravity. This can increase intrapleural pressure and also intra- alveolar pressure at the base of the lungs. The force of gravity increases the amount of air required to ventilate the dependent portion of the lung. This research aims to provide nursing care to An. MK with a diagnosis of pneumonia at the PICU Room, R.D. Kandou Manado Hospital. This research uses a descriptive research design with a case study approach. The analysis technique used is observation and summary studies which produce data for further interpretation and comparison with existing theory. This research found that respondents showed that their breathing patterns improved after being given the semi-Fowler position for 2 days with a frequency of 2 times a day, 15-20 minutes for respondents. Setting the semi-Fowler position can solve the problem of ineffective breathing patterns in pneumonia patients.